2018
DOI: 10.5688/ajpe6274
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Based Differences Among Pharmacy Students Involved in Academically Dishonest Behavior

Abstract: To determine whether differences based on gender exist among pharmacy students involved in cases of admitted cheating or other academic dishonesty and to assess perceptions of academic dishonesty. Two cohorts of second-year male and female pharmacy students from four Northern California pharmacy programs were invited to complete a 45-item cross-sectional survey. Descriptive statistics and Pearson's chi-squared test were used for statistical analysis. There were 330 surveys completed with a 59% response rate. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…Most of the respondents were female (77%) and according to (Whitley et al, 1999 ), females are generally more helpful and supportive displaying enhanced collectivistic traits. However, no association was seen between gender and cheating behavior as has also been reported by others (Ip et al, 2018 ; Özcan et al, 2019 ).…”
Section: Discussionsupporting
confidence: 68%
“…Most of the respondents were female (77%) and according to (Whitley et al, 1999 ), females are generally more helpful and supportive displaying enhanced collectivistic traits. However, no association was seen between gender and cheating behavior as has also been reported by others (Ip et al, 2018 ; Özcan et al, 2019 ).…”
Section: Discussionsupporting
confidence: 68%
“…Although this intervention technique seems sound in a specific discipline such as accounting, it appears defective across entire fields of study and in traditionally male-dominated careers. In contrast, in another study, Ip et al (2018) stated that there is no statistically significant gender difference regarding engaging in various forms of dishonesty behaviors in college. The reason could be that dishonesty contextual factors can influence academic dishonesty.…”
Section: Discussionmentioning
confidence: 85%
“…The study concluded that cheaters possessed lower mastery motivation and higher extrinsic motivation. These findings suggest the need to foster students' awareness of unprofessional attitudes, including cheating and academic misconduct [25].…”
Section: Discussionmentioning
confidence: 94%